PHARMACOLOGICAL ACTION OF VAMANA DRUGS - Sharma Ravidutt; Gaur Bhaskar; Parida Akhilanath; Jena Satyasmita; Gupta Arvind Kumar (International Journal of Applied Ayurved Research, 2019)
Ayurveda has its own principles of treatment. The basic principle, of all Ayurvedic treatments, is to augment the deficiency, to suppress the aggravation and reduce the increment of Doshas and also maintain the equilibrium of Doshas in the state of health. Vamana occupies the place of uno among all the elimination therapeutic techniques and requires special care during the process. It must be conducted under the supervision of practically trained physician; otherwise a number of complications will arise. Vamana is indicated for elimination of Doshas not only in disease states but also in healthy persons where Kapha is aggravated within normal limits such as in Vasanta Ritu for prevention of disease and maintenance of health. There are six vamana drugs are described by Acharya Charaka acting through Ushna, Teekshana, Sookshama, Vyavayi, Vikasi and Saratva gunas. These drugs act as a primary choice in different disorders.